Development of Herbal Cream with Antifungal Properties for the Treatment of Fungal Infections - Gupta, Bharti (International Journal of Pharmaceutical & Biological Archive, 2024)
Assessing skin and soft-tissue infections can be difficult. Turmeric, neem, and Terminalia arjuna bark possess significant antioxidant, anti-inflammatory, antibacterial, and antifungal activities, which substantially diminish fungal infections. The objective of the study was to develop an environmentally friendly antiseptic cream by utilizing turmeric, neem extract, T. arjuna bark, castor oil, coconut oil, and glycerine as a natural preservative, along with fish oils. The physicochemical qualities of the herbal antiseptic cream, a thick semisolid substance, were examined. These features included color, odor, pH level, ability to be squeezed out, thickness, capacity to spread, ability to dissolve, and ability to be washed off. The study conducted antimicrobial activity tests against Tinea species and fungus in microbiological culture and determined that eco-antifungal cream is compatible. The zone of inhibition was determined and administered to individuals with Tinea psoriasis. The product’s quality assessment revealed no observable alterations, appropriate pH levels, commendable spreadability, uniformity, and efficacy in addressing skin infections in patients. The viscosity of creams is directly proportional to the shear rate, meaning that as the shear rate decreases, the cream viscosity increases. Stability analyses were performed on creams containing plant extracts, which exhibited antifungal characteristics and could function as a protective shield against fungal infections.